Gestão escolar na perspectiva da pedagogia de projetos: interlocuções e práticas em uma escola do campo - Santos, Fabíola Ramalho dos (2018)
This research had the general objective of investigating the school management process from the perspective of pedagogy of projects in the context of Nossa Senhora do Carmo School, located in the rural area of Bananeiras, Paraíba. Specifically, it aimed to relate the role of democratic school management in the pedagogical perspective of projects and their implications for the education of the field and to reflect on the importance of pedagogy of projects as a democratic space for community participation in school management processes. education in the field. In this way, it is characterized as a field research, of descriptive exploratory character, whose analyzes started from the qualitative approach of the data in the light of theoretical approaches of Popular Education, of the Democratic Management and Project Pedagogy. As data collection procedures, bibliographical and documentary research was carried out, direct and non-participant observation, as well as semi-structured interviews with the 3 counselors of Nossa Senhora do Carmo School. It is concluded that Nossa Senhora do Carmo School develops a democratic-participative management and has mechanisms of participation of the school community that work in an effective way to guarantee the exercise of participation and citizenship, consequently, promoting the process of democracy. Therefore, the methodological context of the Pedagogy of Projects carried out in said school presents a pedagogical work articulated with all segments of the school, especially with the management, in order to develop a methodology based on educational projects that try to reconstruct the teaching-learning processes, as a step towards an innovative education. In this way, Project Pedagogy starts from the interest and reality of its students, understanding them as knowledge- building beings and teachers as mediators of scientific knowledge.